The Crucial Role of Methodology Development in Directed Evolution of Selective Enzymes. Issue 32 (26th March 2020) - Qu, Ge; Li, Aitao; Acevedo‐Rocha, Carlos G.; Sun, Zhoutong; Reetz, Manfred T.
Abstract: Directed evolution of stereo‐, regio‐, and chemoselective enzymes constitutes a unique way to generate biocatalysts for synthetically interesting transformations in organic chemistry and biotechnology. In order for this protein engineering technique to be efficient, fast, and reliable, and also of relevance to synthetic organic chemistry, methodology development was and still is necessary. Following a description of early key contributions, this review focuses on recent developments. It includes optimization of molecular biological methods for gene mutagenesis and the design of efficient strategies for their application, resulting in notable reduction of the screening effort (bottleneck of directed evolution). When aiming for laboratory evolution of selectivity and activity, second‐generation versions of Combinatorial Active‐Site Saturation Test (CAST) and Iterative Saturation Mutagenesis (ISM), both involving saturation mutagenesis (SM) at sites lining the binding pocket, have emerged as preferred approaches, aided by in silico methods such as machine learning. The recently proposed Focused Rational Iterative Site‐specific Mutagenesis (FRISM) constitutes a fusion of rational design and directed evolution. On‐chip solid‐phase chemical gene synthesis for rapid library construction enhances library quality notably by eliminating undesired amino acid bias, the future of directed evolution? Abstract : Take the structure‐guided route : Application of advanced gene mutagenesis methods and strategies ensures speed and reliability in laboratory evolution of selective enzymes as catalysts in organic chemistry and biotechnology. Recent developments in novel methodology from sequence‐based to structure‐guided methods are presented in this Review.